Wedding Venue Berbasis Nusantara di Ungasan, Kabupaten Badung - Simanjuntak, Dehny Magdalena; Anom Rajendra, I Gusti Ngurah; Djaja Bharuna, Anak Agung Gde (Jurnal Arsitektur Universitas Udayana; Vol 9 No 02 (2021): Jurnal Arsitektur, Universitas UdayanaDO - 10.24843/jaunud.v9i02.66460, 2021)
Bali which known as the island of the gods is in demand by many tourists. One of which is those who want a memorable wedding. The design of this wedding venue is very much needed in Bali, especially in the Ungasan area. This is because there are no complete facilities to accommodate the prospective bride and groom in preparing for their wedding. To give identity to this design, the concept of Traditional Architecture is applied to buildings in the Wedding Venue area. The goal is that every bride who chooses this area will not only get an impression of the beautiful island of the gods but also have an impression of the soul of traditional architecture in Indonesia. In achieving this goal, the morphological selection of building forms from traditional architecture is applied, including traditional Balinese architecture, Joglo house architecture, and Rumah Bolon architecture. The choice of three different concepts in one area is because this area has three different main activities but they are united in one area. It is hoped that this wedding venue will be able to meet the needs of the prospective bride and groom and become a place to unite two people in one marriage. Keywords : Wedding Venue, Balinese Traditional House, Joglo Traditional House, Bolon Traditional House.